An analysis on the challenges to gender balance in the African Union standby force: a case of the SADC Brigade 2003-2017 - Mwarweye, Grace M. (Midlands State University, 2019)
This study analyses the challenges of gender balance in the African Standby Force with specific reference to the SADC Standby Force from the period of 2003 to 2017. Gender balance in other peacekeeping forces is also noted in this paper. The African Standby Force was established for the reason of solving Africa’s problems that is African solutions to Africa’s problems. As per Article 13 of the Protocol relating to the establishment of the Peace and Security Council of the African Union, the ASF is based on standby arrangements with Africa’s five sub-regions. This supports the Pan African ideology raised by African heads’ of states. The Standby Force consists of three components which are the civilian, police and military and it is also there for peacemaking and peacekeeping but it lacks gender balance. A low number of women are recruited in national deference forces leading to non or few women deployed to the standby force. This is due to several reasons which are societal norms, patriarchy, religion, women being afraid of being abused and gender based roles. Long before colonialism women would take part in battles some would actually lead without any problems and would also conquer. Everything changed when Christianity was introduced in Africa. Patriarchy has always been there and to a certain extent it controlled women. Qualitative research method was used in order to gather data for the research paper. Primary and secondary sources were used as sources of information. Primary sources used were interview and questionnaire and secondary sources used were books, credible websites and journal articles. On the other hand liberal feminism and the concept of patriarchy were used to get a deeper understanding of the research topic and as a theoretical framework analysis. Liberal feminism illustrates that men and women should work side by side equally. The concept of patriarchy notes that because of the patriarchal society there is gender inequality in peacekeeping operations. This study recommends that there should be both equality and equity in the SADC Standby Force. Policies that have been put into place should be taken into action in order to have gender balance.